Financial Status and Literacy, and Retirement Preparedness of Generation X Government Employees - Abad, Leorena Kyla L.; Angelito, Lady Angelique L.; Arceno, Mae D.; Sumicad Jr, Eligen H (AKTIVA: Journal of Accountancy and Management, 2025)
Purpose: To investigate the relationship between financial literacy and retirement preparedness of Generation X government employees.Design/methodology/approach: This study employed a quantitative research design. Specifically, the descriptive-correlational design uses survey data. This allows the exploration of associations between variables without manipulation, offering insights into how these variables interrelate and influence retirement preparedness. A survey was conducted using a questionnaire administered via printed forms.Research Findings: Generation X government employees have high financial literacy but varying levels of retirement preparedness. A significant positive correlation exists between financial literacy and retirement preparedness.Contribution/Originality/Novelty: The study fills the gap in the literature by focusing on a specific demographic, the Generation X government employees in the Philippines. Tujuan Penelitian: Untuk menyelidiki hubungan antara literasi keuangan dan kesiapan pensiun pegawai pemerintah generasi X.Desain / metodologi / pendekatan: Penelitian ini menggunakan desain penelitian kuantitatif, khususnya desain deskriptif-korelasional, dengan menggunakan data survei. Pendekatan ini memungkinkan eksplorasi hubungan antar variabel tanpa manipulasi, sehingga memberikan wawasan tentang bagaimana variabel-variabel ini saling berhubungan dan memengaruhi kesiapan pensiun. Survei dilakukan dengan menggunakan kuesioner yang disebarkan dalam bentuk cetak.Temuan Penelitian: Pegawai pemerintah Generasi X memiliki literasi keuangan yang tinggi tetapi tingkat kesiapan pensiun mereka bervariasi. Ada korelasi positif yang signifikan antara literasi keuangan dan kesiapan pensiun.Kontribusi / Orisinalitas / Kebaruan: Penelitian ini mengisi kesenjangan dalam literatur dengan berfokus pada demografi tertentu, pegawai pemerintah Generasi X di Filipina.